The relationship between geodiversity and biodiversity: A theoretical approach - Ivanović Marko (Bulletin of Natural Sciences Research)
The relationship between geodiversity and biodiversity is often considered within geoecological frameworks. Their interaction within real space forms the natural structure of landscapes. Although they are defined as two separate and equivalent systems with different structures, their relationship makes them interdependent, with geospatial distribution being the common point of contact. The term "geodiversity" is relatively recent, defined as the desire to express the opponent of the diversity of the living world - biodiversity. Thus, through a holistic concept, it is possible to observe multiple levels of interaction between geodiversity and biotic resources, revealing their interrelationship. The challenges of researching both geodiversity and biodiversity are characterized by similar shortcomings. Based on the previous researches of different authors, the work aims to define in the best possible way a biotic-abiotic relationship as an essential component in the concept of nature, the sphere of their connection and joint action. However, due to the numerous fields of their interaction, the work only partially defines them, without analyzing each field of interaction, in detail. In addition, the connection of these two concepts also requires interdisciplinary cooperation, the goal of which must be to improve the understanding of biodiversity and geodiversity, and their integration in evaluation, with the common goal of protecting and preserving nature as a whole and its individual parts. To a significant extent, these can be addressed through the application of geoinformatics tools, methods, and techniques, especially Remote Sensing (RS) and Geographic Information Systems (GIS), which offer the possibility of more adequate evaluation and interpretation of results.